Design, identification, and control of a linear dual-stage actuation positioning system. Issue 12 (August 2018) - Zheng, J.; Fu, M.; Lu, R.; Xie, S.
Abstract: Voice coil actuators (VCAs) are widely used for motion control applications that require high precision and fast acceleration. However, they have one disadvantage of short travel ranges typically on the order of centimeters. To overcome this disadvantage, this paper employs an existing concept called dual-stage actuation and combines a linear VCA with a low-cost dc-motor (DCM) to construct a linear dual-stage actuation (DSA) positioning system, which extends the travel range as large as that provided by the DCM while retaining the positioning accuracy offered by the VCA. For this setup, proper controllers are crucial to achieve the desired performance. Hence, we first identify the DSA model and investigate the interaction force between the VCA and DCM stage. Next, robust controllers are specifically designed for the DCM and VCA stage, respectively. Finally, experiments are carried out to verify the robust tracking performance of the developed linear DSA positioning system. It is demonstrated that the developed DSA positioning system offered a cost-effective solution to extending the working range of the existing VCA whilst retaining the positioning accuracy.